Early Growth Characteristics of Corn Under Different Arbuscular Mycorrhizal Fungi (AMF) Inoculant Sources in a Conventional Cultivation System - Marlin Sefrila; Mesye Marizka Olivya; A. Napoleon; Rofiqoh Purnama Ria; Santa Maria Lumbantoruan (Biosel Biology Science and Education, 2026)
Arbuscular Mycorrhizal Fungi (AMF) are widely recognized as biological agents that improve nutrient uptake, particularly phosphorus, and enhance plant adaptation under suboptimal soil conditions. This study aimed to evaluate the effects of different inoculant sources on the early vegetative growth of corn under a conventional cultivation system. A randomized complete block design was used with five inoculant treatments: unsterilized soil, sterilized soil, tidal soil, local tidal AMF propagules, and commercial mycorrhizae, with four replications. The observed variables included plant height, leaf number, stem diameter, and leaf greenness at 2, 3, and 4 weeks after planting (WAP). The results showed that inoculant source significantly affected plant height, leaf number, and stem diameter at 4 WAP. Leaf greenness was not significantly affected by treatment at all observation periods. Tidal soil treatment resulted in the highest plant height (53.92 cm), leaf number (6.58 leaves), and stem diameter (43 mm) at 4 WAP. Growth in unsterilized and sterilized soil treatments was relatively similar. Lower performance of local AMF propagules and commercial mycorrhizae may be associated with differences in inoculum compatibility; however, root colonization was not quantitatively measured in this study. These findings indicate that tidal soil has potential as a biological inoculant source for early corn growth under conventional cultivation.  Keywords: Biological Inoculation, Root Symbiosis, Plant Physiology, Soil Fertility